Michael Riffaterre’s Semiotics on William Shakespeare’s A Madrigal (A Semiotic Analysis on Poetry) - Putri Intan Sari Pradani; Sarif Syamsu Rizal (Culturalistics: Journal of Cultural, Literary, and Linguistic Studies, 2020)
AbstractThis study is entitled “Michael Riffater's Semiotics on William Shakespeare's A Madrigal (A Structural and Semiotics Criticism on Poetry)”. The purpose of this study is to find out what aspects of Michael Riffaterre's semiotics are composed in William Shakespeare's A Madrigal poem. This study uses a qualitative descriptive method to describe the semiotic aspects, and library research to collect data. In order to achieve the objectivity of this study, the literary study approach used is structural and semiotic approach. The structural approach directs the description of aspects of the physical appearance and the semiotic approach limits the description of the semiotic aspects in William Shakespeare's A Madrigal. The results of the study show that there are four aspects and their sub-aspects found in William Shakespeare's A Madrigal. The first aspect is the result of Heuristic and Hermeneutic readings and there are three sub-aspects found, namely Syntax Extraction, Morphological Change, and Normative and Semantic Forms. The second aspect is Indirect Expression including three sub-aspects that are found, namely Shifting Meaning, Distorting Meaning, and Creating Meanings. The third aspect is Matrix, Variants and Models. The fourth aspect is Potential and Actual Hypogram.Keywords: Semiotics; Michael Riffatere; Mandrigal